Current developments of bioanalytical sample preparation techniques in pharmaceuticals - Ingle, Rahul G.; Zeng, Su; Jiang, Huidi; Fang, Wei-Jie (Journal of pharmaceutical analysis, 2022)
Sample preparation is considered as the bottleneck step in bioanalysis because each biological matrix has its own unique challenges and complexity. Competent sample preparation to extract the desired analytes and remove redundant components is a crucial step in each bioanalytical approach. The matrix effect is a key hurdle in bioanalytical sample preparation, which has gained extensive consideration. Novel sample preparation techniques have advantages over classical techniques in terms of accuracy, automation, ease of sample preparation, storage, and shipment and have become increasingly popular over the past decade. Our objective is to provide a broad outline of current developments in various bioanalytical sample preparation techniques in chromatographic and spectroscopic examinations. In addition, how these techniques have gained considerable attention over the past decade in bioanalytical research is mentioned with preferred examples. Modern trends in bioanalytical sample preparation techniques, including sorbent-based microextraction techniques, are primarily emphasized. [Display omitted] •Bioanalytical sampling techniques are described with suitable applications in pharmaceuticals.•The pros and cons of each bioanalytical sampling techniques are described.•Relevant biological matrices are outlined.